Hydration characteristics of bagasse in cement-bonded composites (2013)
Four compatibility assessment methods were used to ascertain the compatibility of bagasse with cement composite. The time to reach maximum hydration temperature was achieved when CaCl2 and water above 60℃ were used as treatment agents. Maximum hydration temperature between 55℃ – 61℃ were achieved when treated with 1 – 3% CaCl2. The inhibitory index value of 1.58% - 8.83% were achieved when treated with bagasse while others have value greater than the acceptable parameter standard for exterior use. The maximum hydration rate of 4.0 was achieved when the bagasse fiber was treated with 3% CaCl2 and this was closely followed by 2% CaCl2 at 3.38. These results showed that all the different compatibility assessment parameters adopted indicated that bagasse was incompatible with Portland cement without pre treatment. Treatment of bagasse with cold water and addition of 2% CaCl2 satisfied all requirements for compatibility in terms of time to reach maximum temperature, the maximum hydration temperature and the inhibitory index value. Treatment with CaCl2 gave the best result probably due to its capacity to minimize the adverse effect of the soluble sugars and extractives and also to accelerate cement hardening and setting. This result shows that treated bagasse is compatible with cement bonded composite for construction purposes